2018
DOI: 10.1007/s00125-018-4752-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-arginine on energy metabolism, skeletal muscle and brown adipose tissue in South Asian and Europid prediabetic men: a randomised double-blinded crossover study

Abstract: Aims/hypothesisIndividuals of South Asian origin are at increased risk of developing type 2 diabetes mellitus and associated comorbidities compared with Europids. Disturbances in energy metabolism may contribute to this increased risk. Skeletal muscle and possibly also brown adipose tissue (BAT) are involved in human energy metabolism and nitric oxide (NO) is suggested to play a pivotal role in regulating mitochondrial biogenesis in both tissues. We aimed to investigate the effects of 6 weeks of supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…In concordance, serum sclerostin levels positively correlated with skeletal muscle and adipose tissue insulin resistance in a hyperinsulinemic-euglycemic clamp study in human subjects with either normoglycemia or prediabetes [13]. Alternative mechanisms that may contribute to peripheral insulin resistance in South Asians are a pro-inflammatory status, including downregulation of genes involved in anti-inflammatory type 1 interferon signaling in WAT and skeletal muscle [35], lower adiponectin levels [36,37], as well as a lower skeletal muscle oxidative capacity [38] and cardiorespiratory fitness compared with white Caucasians [39].…”
Section: Discussionmentioning
confidence: 99%
“…In concordance, serum sclerostin levels positively correlated with skeletal muscle and adipose tissue insulin resistance in a hyperinsulinemic-euglycemic clamp study in human subjects with either normoglycemia or prediabetes [13]. Alternative mechanisms that may contribute to peripheral insulin resistance in South Asians are a pro-inflammatory status, including downregulation of genes involved in anti-inflammatory type 1 interferon signaling in WAT and skeletal muscle [35], lower adiponectin levels [36,37], as well as a lower skeletal muscle oxidative capacity [38] and cardiorespiratory fitness compared with white Caucasians [39].…”
Section: Discussionmentioning
confidence: 99%
“…In the pig, oral L-arginine supplementation during gestation increased the weight of piglets and placentas at birth 2224 . Moreover, long-term supplementation with L-arginine has been shown to reduce glucose and insulin plasma concentrations following an oral glucose tolerance test in humans 25,26 . L-arginine supplementation could thus increase birthweight and improve maternal metabolism during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed no mean differences in SUV of BAT ( p > 0.05) following a high calorie (1622 ± 222 kcal) carbohydrate rich meal [ 31 ], a standard (545 kcal) meal [ 29 ] and during 200% overfeeding [ 45 ] ( Figure 3 ). Finally, one study [ 42 ] offered data for a meta-analysis from two different groups of participants, investigating the effects of a 6-week supplementation of L-Arginine on BAT activity, which showed no mean differences in SUV of BAT ( p > 0.05; Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…One RCT [40] and one CSS [41] examined the effects/associations of dietary factors on BAT activity through measurements of core and skin temperatures. Five RCTs [29,[42][43][44][45], one CSS [46], one CT [47] and one SGDS [31] studied the effects/associations of dietary elements on BAT activity using PET/CT, while a SGDS [32] used infrared camera for BAT assessments. One SGDS [48] and one CSS [49] examined the effects/associations of dietary factors on BAT activity via measurements of UCP1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%